(untitled) (Sebha University Conference Proceedings, 2025)
In this paper, we study a new low-complexity algorithm to reduce computational complexity in a maximum-likelihood (ML) decoder used in fully generalized spatial modulation (FGSM) and fully quadrature spatial modulation (FQSM). The computational complexity was reduced based on the maximum ratio combining (MRC) algorithm where the detection process has been divided into two stages including active antennas detection and modulated information bits detections. The active antennas detections are processed using MRC while modulated information bits have been detected using the conventional ML scheme. The outperformance of the proposed approaches is validated via simulation in term of computational complexity and energy efficiency compared against their benchmarks which employ the optimal ML detector at the receiving end.